Thoughts Regarding Amendment in Non-Pecuniary Damages on Turkish Administrative Judicial Procedure Law - Seyit Rasim Doru (İbn Haldun Çalışmaları Dergisi)
There are two types of lawsuits in Turkish Administrative Procedural Law, namely annulment lawsuit and full remedy lawsuit. In full remedy lawsuits, the compensation requested is both pecuniary and non-pecuniary. The amendment of pleadings in full remedy lawsuits can be used by increasing the requested amount once until the final decision. This possibility to increase the amount of the claim has been introduced later in the Turkish Administrative Judicial Procedure Law. After the introduction of this regulation, it has been discussed whether it can be applied to non-pecuniary damages claims. In order to express these, we will first examine the concept of amendment in civil procedure law in general and its application by substantiating with the Court of Cassation rulings. Then the Council of State will be set forth. Subsequently, we will express our views on this area of debate, where the judicial and administrative judiciary have different decisions, that amendment in non-pecuniary damages should be possible in terms of administrative judiciary, that although it is made once as a rule, it can be made again in case new events arise, that this right should sometimes be recognized at the appeal stage too, and that this request can be asserted later, even if it is not included in the first petition.